Pengembangan PowerPoint Interaktif Berorientasi terhadap Pemahaman Konsep Dasar Persamaan Diferensial Parsial - Lu'luilmaknun, Ulfa; Kertiyani, Ni Made Intan; Arjudin, Arjudin (FKIP Universitas Mataram, 2024)
The understanding of partial-differential equation basic concept is the basic knowledge needed to understand and determine general solutions on partial-differential equations. From the observation on the partial-differential equation class, there are still some students who are unable to understand the basic concept of partial-differential equation. This study aims to discover how the development of interactive PowerPoint learning media is oriented to the basic concept understanding of partial-differential equation. This study was an R&D research using 4D model by Thiagarajan through some stages namely define, design, develop, and dissemination. The instruments used were media expert and material expert validation sheets, student and practitioner response questionnaires, and Quizizz-assisted tests. There were 14 slides on the results of interactive PowerPoint development which contained the title of materials delivered, the learning goals to be achieved, interactive activities, evaluation and references. The interactive PowerPoint learning media can be said to be valid by media expert judgments and material expert judgments, and is practical to use according to the results of student and practitioner response questionnaires. Interactive PowerPoint media is also effective in helping understand the basic concepts of PDP.